PROFIL KEBUGARAN JASMANI SISWA KELAS V DAN VI MELALUI INSTRUMEN TES KEBUGARAN JASMANI INDONESIA (TKSI) FASE C DI SD NEGERI 178492 PAGAR BATU - Hutagalung, Novan Trisan; Khairul Usman (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the physical fitness profile of 5th and 6th-grade students at SD Negeri 178492 Pagar Batu based on the Indonesian Student Fitness Test (TKSI) Phase C instrument. This descriptive quantitative research applied a one-shot case study approach. The research population included all 58 students in grades 5 and 6. Total sampling was utilized to select the sample. Data collection involved five components of the TKSI Phase C test: the Child Ball Test, Tok-Tok Ball Test, Move The Ball Test, Shuttle Run Test, and 600-Meter Run Test. Data analysis was conducted using descriptive quantitative statistics in the form of percentages. The results showed that the students' physical fitness profile was generally in the "Good" category. Specifically, 8 students (13.79%) were in the "Very Good" category, 24 students (41.38%) in "Good", 22 students (37.93%) in "Moderate", 4 students (6.90%) in "Poor", and no students (0%) in "Very Poor". The most optimal result was found in the Shuttle Run Test, while the lowest performance was observed in the 600-Meter Run Test. These findings can serve as a reference for teachers to design structured physical training programs.